(untitled) (American Journal of Business Management, Economics and Banking, 2023)
The research deals with the concept and importance of industrial specialization for auditors, as well as the concept of audit risks and its divisions. It also deals with the role of industrial specialization in reducing audit risks. It argues that industrial specialization plays a major role in controlling related risks. Previous studies showed that a specialized auditor can detect fraud in financial reports due to his/her experience in the client’s field of activity and as a result of his/ her continuous review of homogeneous activities. Specialized auditors, when practicing their professional work within their field of specialization, have sufficient experience, and also the ability to detect fraud compared to auditors with little experience. However, when specialized auditors practices the audit process outside their field of specialization, the degree of their professional competence decreases, as does their ability to study and analyze the causes of fraud. The study also concludes that a specialized auditor can control the risks of the business of the entity under review by studying and analyzing the administrative aspects of the client, as well as integrity and competition in the industry and the financial trends of the entity. In addition to the above, if an auditor acts as a specialized auditor, he/she will have the ability to control the risks of his/her work.